Flexing Harta di Media Sosial: Anak Kunci Pembuka Kotak Pandora - Widya Romasindah Aidy; Kardinah Indrianna Meutia; Mic Finanto Ario Bangun; Amalia Syauket (KRTHA BHAYANGKARA, 2023)
Still at the beginning of 2023, various social media shows the phenomenon of showing off wealth or flexing assets carried out by Pandora, such as wives and even children of public officials. Flexing property is a behavior that shows like to show off as a luxurious lifestyle tends to be arrogant and flexing behavior is one of the triggers for greed. Greedy behavior is the cause of corruption. Flexers unknowingly reveal their personalities when creating content on social media, which has the potential to cause various disasters if they go too far and cause unexpected problems. It's like Pandora's box, once opened, various kinds of disasters that befell Pandora come out and are very difficult to resolve. Even like a boomerang that reveals his shame. This phenomenological research uses a descriptive approach, relying on library data to describe the phenomenon of Pandora's luxurious lifestyle, namely the wives of public officials and their families. The results of this research conclude that Pandora's behavior has exposed her own disgrace, and is not in accordance with the ethics of public officials